ETHNOMATHEMATICS EXPLORATION OF THE ISTIQLAL MOSQUE JAKARTA - Tuhfatul Janan (AL JABAR: Jurnal Pendidikan dan Pembelajaran Matematika, 2024)
Ethnomathematics is a branch of mathematical study that was developed in a cultural context. This research aims to explore the concept of ethnomathematics in the Istiqlal Mosque in Jakarta. The method used is descriptive exploratory with an ethnographic approach, which aims to explore information thoroughly to describe and analyze cultural elements in society. Data collection techniques include two types, namely library data collection through literature studies and field data collection through observation and documentation. The collected data is then analyzed using the data reduction method, which involves sorting, centralizing, and simplifying information. The results of the study show that the structure and ornaments of the Istiqlal Mosque Jakarta contain various flat and spatial structures, such as half-spheres, tubes, rectangles, and circles. Keywords: Ethnomathematics, Geometry, Istiqlal Mosque Jakarta